The Anthropometric Changes among Women of Reproductive Age Using Contraceptives in Nyeri County, Kenya: A Six-Month Prospective Study - LANG'AT, Purity CHEPKORIR; MBITHE DAVID-KIGARU, Dorcus; NDUNG’U, Zipporah; KIMETO, Pamela (African Journal of Nutrition and Dietetics, 2025)
Nutritional status is a vital determinant of reproductive health among women of reproductive age (WRA), yet limited data exist on how hormonal contraceptive use influences anthropometric outcomes in African populations. This study assessed changes in body mass index (BMI), waist circumference (WC), and weight among WRA in Nyeri County, Kenya, using hormonal, non-hormonal, or no contraceptives. A six-month prospective study was conducted among 114 women of reproductive age (18–49 years) at baseline, with 104 completing follow-up. Participants were categorized as hormonal users, non-hormonal users, or non-users. Anthropometric measures (weight, BMI, waist circumference) were assessed using World Health Organization protocols. Data were analyzed using paired t-tests, ANOVA, and multivariate linear regression, controlling for dietary diversity and physical activity. At baseline, 68.3% of women used contraceptives (36.0% hormonal, 32.5% non-hormonal). Hormonal users gained an average of 1.18 kg (95% CI: 0.04–2.32; p = 0.043) and 0.52 kg/m2 BMI (95% CI: 0.03–.01; p = 0.038) compared to non-users, after adjusting for confounders. Waist circumference changes were non-significant. Obesity prevalence by BMI rose marginally from 29.8% to 30.8%, while WC-based obesity increased from 34.6% to 37.5%. These findings suggest marginal associations that remained insignificant after adjustment for multiple comparisons. Hormonal contraceptive use was independently associated with modest increases in weight and BMI over six months, though not significantly. These findings support integrating routine anthropometric monitoring into family planning services and counseling women on lifestyle modifications to mitigate weight-related concerns.